Clinical, Double-blind, Placebo-controlled Study Investigating the Combination of Acetylsalicylic Acid and Pseudoephedrine for the Symptomatic Treatment of Nasal Congestion Associated with Common Cold - Loose, Irene; Winkel, Matthias (Arzneimittelforschung, 2004)
It was the aim of this clinical study to demonstrate the efficacy of 1000 mg acetylsalicylic acid (ASA, CAS 50-78-2) in combination with 60 mg pseudoephedrine (PSE, CAS 90-82-4), compared with placebo, in the symptomatic treatment of nasal congestion associated with the common cold. A further aim was to demonstrate the efficacy of 500 mg ASA + 30 mg PSE and of 1000 mg paracetamol (CAS 103-90-2) + 60 mg PSE (active control) in the symptomatic treatment of nasal congestion. The study was designed as a randomized, two-center, double-blind, double-dummy, placebo-controlled, parallel-group, single-dose efficacy and safety trial over 6 h and was carried out in the USA. In total, at two centers, 643 patients who had a history and diagnosis of acute upper respiratory tract infection (URTI), were included; they showed symptoms such as nasal congestion, scratchy/sore throat, headache, generalized muscle ache, earache, runny nose, fever, sneezing etc. The investigational drugs ASA and PSE were both provided as granules in sachets and the granules were dissolved in water before administration; the combined preparation of paracetamol + PSE was administered as commercially available tablets encapsulated for blinding. For all preparations, matching placebos were provided. The primary efficacy variable was the area under the curve for differences from baseline on a nasal congestion scale in the first 2 h after treatment.To be eligible for the study, otherwise healthy volunteers were to present with nasal stuffiness of recent onset that reached a score of at least 6 on the 11-point scale for nasal congestion (0 = not stuffy, 10 = very stuffy). The primary analysis of the primary efficacy variable was calculated by analysis of variance including treatment group, severity (moderate/severe) and center as main strata. The analysis was performed using the intent-to-treat population.All active treatments proved to be statistically significantly superior to placebo with regard to the primary efficacy variable. Significant superiority of active treatment compared with placebo could also be demonstrated for an interval of up to 6 h after intake of the drug and for the relief of nasal congestion. The lower dose did not reveal significant different results compared with placebo for relief of nasal congestion in patients with a severe nasal congestion score at baseline. As well in patients with moderate nasal congestion score (NCS) at start of the study the difference from baseline in the NCS compared with placebo was not statistically significant. Thus a trend towards better efficacy in the higher dose could be assumed. No difference was found between 1000 mg ASA + 60 mg PSE and the active control. There were no differences between the two centers. The treatment proved to be safe and well tolerated, without relevant differences between the four treatment groups. Main adverse events were found to be related to the upper respiratory tract infection or were of gastrointestinal nature. In conclusion, the combination of ASA with PSE can be considered as an effective and safe remedial for the symptomatic treatment of the nasal congestion during URTI.
Keywords: Acetylsalicylic acid, clinical studies, combination with pseudoephedrine; CAS 50-78-2; CAS 90-82-4; CAS 103-90-2; Nasal congestion, associated with common cold; Paracetamol, clinical studies, combination with pseudoephedrine; Pseudoephedrine, clinical studies, combination with acetylsalicylic acid